Pengaruh Influencer Media Sosial Dalam Pengambilan Keputusan Mahasiswa - Ulia, Isma Rizqiatul; Syafalah, Zagar; Sefiana, Lia; Chansa, Talita Putri; Sari, Aslinda Gangga; Nugraha, Joko Tri (FIA Unkris Press, 2025)
The rapid development of science and technology has led to globalization in various aspects of life. In the era of growing technological innovation, the phenomenon of social media influencers has emerged, which has a significant ability to influence public opinion. Influencers are individuals who have the ability to influence the behavior of their followers through the content they share on social media. This study aims to determine the level of student satisfaction with promotions carried out by influencers, find out how much influence influencers have on student decision making, and find out what social media platforms students use. This study uses a quantitative approach through distributing questionnaires to state administration students. The results of the study are expected to provide an overview of how State Administration students respond to the influencer phenomenon on various social media platforms. This research provides insight into consumer behavior, especially students who are active in using social media, and shows the importance of influencer-based marketing strategies in influencing purchasing decisions. Influencers have the power to shape opinions and preferences of young consumers, especially among university students. The results of this study can be utilized by industry players to design more effective and relevant marketing strategies in the digital era. However, there are some limitations in this study, such as the use of online questionnaires that limit direct interaction with respondents. This is in line with the findings of previous studies which state that limitations in online data collection methods can reduce the depth of information obtained and less reflect the overall psychological condition of respondents.